The effect of harmonized emissions on aerosol properties in global models - An AeroCom experiment - Textor, C; Schulz, M; Guibert, S; Kinne, S; Balkanski, Y; Bauer, S; Berntsen, T; Berglen, T; Boucher, O; Chin, M; Dentener, F; Diehl, T; et al. (2007)
The effects of unified aerosol sources on global aerosol fields simulated by different models are examined in this paper. We compare results from two AeroCom experiments, one with different (ExpA) and one with unified emissions, injection heights, and particle sizes at the source (ExpB). Surprisingly, harmonization of aerosol sources has only a small impact on the simulated inter-model diversity of the global aerosol burden, and consequently global optical properties, as the results are largely controlled by modelspecific transport, removal, chemistry (leading to the formation of secondary aerosols) and parameterizations of aerosol microphysics (e.g., the split between deposition pathways) and to a lesser extent by the spatial and temporal distributions of the (precursor) emissions. The burdens of black carbon and especially sea salt become more coherent in ExpB only, because the large ExpA diversities for these two species were caused by a few outliers. The experiment also showed that despite prescribing emission fluxes and size distributions, ambiguities in the implementation in individual models can lead to substantial differences. These results indicate the need for a better understanding of aerosol life cycles at process level (including spatial dispersal and interaction with meteorological parameters) in order to obtain more reliable results from global aerosol simulations. This is particularly important as such model results are used to assess the consequences of specific air pollution abatement strategies.